2012
DOI: 10.3844/ajavsp.2012.84.91
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to High Grain Diets Proceeds Through Minimal Immune System Stimulation and Differences in Extracellular Matrix Protein Expression in A Model of Subacute Ruminal Acidosis in Non-lactating Dairy Cows

Abstract: Problem statement: Subacute Ruminal Acidosis (SARA) is a metabolic disorder affecting approximately 20% of all dairy cattle in North America. Although the presence of SARA has been described for some time, the etiology of the disorder remains uncertain. For example, many animals diagnosed with SARA seem to remodel and adapt their epithelium to accommodate the stresses imposed by SARA, but not before exacting a significant health and economic toll. Specifically, a search is on in which a desire to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…In addition, SAA, also an acute phase protein, was unaffected by the addition of butyrate. Together, the data for LPS, LBP and SAA contradict earlier findings using similar models (Dionissopoulos et al, 2012a;2012b), that although SARA can have profound effects on the physiology of the rumen, the bacterial overgrowth that typically occurs is not sufficient enough to result in a systemic inflammatory response. The tissue signals generated as a result of SARA at the site of tissue damage (Steele et al, 2011a) likely act locally in an autocrine or paracrine manner.…”
Section: Physiological Parameterscontrasting
confidence: 55%
See 1 more Smart Citation
“…In addition, SAA, also an acute phase protein, was unaffected by the addition of butyrate. Together, the data for LPS, LBP and SAA contradict earlier findings using similar models (Dionissopoulos et al, 2012a;2012b), that although SARA can have profound effects on the physiology of the rumen, the bacterial overgrowth that typically occurs is not sufficient enough to result in a systemic inflammatory response. The tissue signals generated as a result of SARA at the site of tissue damage (Steele et al, 2011a) likely act locally in an autocrine or paracrine manner.…”
Section: Physiological Parameterscontrasting
confidence: 55%
“…SARA does this by causing a sloughing of the rumen epithelium, compromising epithelial integrity (Steele et al, 2011a). Despite the fact that the transmigration of microbes across the rumen wall has been documented in cases of SARA, we have shown that this effect involves the immune system, although the extent of immune system stimulation is limited to local events and is not detectable systemically (Dionissopoulos et al, 2012a;2012b). Experimentally, we have shown that adaptation to a SARA diet takes place within three weeks (Steele et al, 2011a) and previous experiments have shown that one of the principle methods by which the rumen adapts to an acidotic diet is by increasing papillae size and thus the total absorptive surface area of the rumen (Gabel et al, 2002), by increasing cellular turnover and an overall increase in total epithelial cell number (Goodlad, 1981).…”
Section: Introductionmentioning
confidence: 87%
“…Conditions such as acidosis have distinct influences on health and production due to shifts in ruminal and lower gastrointestinal (GI) microbial communities, ruminal fermentation, and ruminal and lower GI function, of which the microbiome and ruminal epithelia have been shown to acclimate in response to SARA (McCann et al, 2016). In turn, acclimation to SARA is facilitated by and linked to the immune system, through crosstalk of inflammatory mediators, endotoxins, epithelial remodeling, and microbial interactions (Dionissopoulos et al, 2012). Crosstalk mechanisms regarding the gut-brain axis are also associated with the potential to affect behavior, through nutritional effects on microbial ecology, ruminal fermentation and morphology, GI inflammation, barrier function, and epithelial gene expression (Devant et al, 2016).…”
Section: Associations With Feed Efficiencymentioning
confidence: 99%